Pengaruh Locus of Control dan Lingkungan Kampus Terhadap Personal Financial Management yang Dimediasi oleh Hasil Belajar Akuntansi Keuangan Menengah 1 Mahasiswa Program Studi Pendidikan Akuntansi - Yuliazizah, Ajeng Mahana; Han Tantri Hardini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to determine the effect locus of control and the campus environment towards personal financial management which is mediated by the learning outcomes of Intermediate Financial Accounting 1. This type of research is quantitative research with data collection techniques using questionnaires. The population of this study were students of the Accounting Education Study Program class 2020 – 2022 who had taken the Intermediate 1 Financial Accounting course and the sampling technique used simple random sampling. The data analysis technique uses SPSS version 29 analysis. The results of the research are 1) there is a positive and significant influence locus of control and AKM 1 learning outcomes towards personal financial management, 2) there is no influence between the campus environment and personal financial management, 3) there is a positive and significant influence locus of control and the campus environment on AKM 1, 4) learning outcomes simultaneously locus of control, campus environment, and AKM 1 learning outcomes influence personal financial management, 5) AKM 1 learning outcomes are able to mediate locus of control and the campus environment towards personal financial management.